The expressiveness of the trait in literacy in drawing in Design (Revista Apotheke, 2023)
This study is part of a doctoral research in Design at the Federal University of Rio Grande do Sul - UFRGS that discusses literacy in drawing, the ability to represent and read the form in the third dimension in the two-dimensional plane, developed in the curricular components of entry of the Design courses. This article deals with the three pillars of drawing literacy in Design: technique, expression and perception. It discusses the expression of the line in hand-made drawings, which demonstrate feelings of those who draw, or even identify the cerebral hemisphere that predominated in the act of drawing. These characteristics observed in expressive drawing are identified in the initial phase of the Design process (sketch). These reflections contextualize the state of the art of these issues, through a bibliographical survey, which contributes to the literacy of drawing in Design graduations; helping the representation and reading of creations in Design; explores the trait, observing its identification, its meaning, its intention and its perception.
Keywords: Observation design; Trace language; Visual expression; Visual communication; Visual perception